Crosslinked fluororesin, method of production and use

CN120504770BActive Publication Date: 2026-10-30JIANGNAN UNIV
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202510877169.3
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2025-06-27
Publication Date
2026-10-30
Estimated Expiration
2045-06-27

AI Technical Summary

Technical Problem

[0003]大部分氟树脂的分子链比较柔顺,玻璃化转变温度较低,只有在较高的结晶度时才能表现出较高的强度,但高结晶度时晶体会通过散射光线使氟树脂的透明度和韧性显著下降,导致大部分商用氟树脂难以兼顾高强度、高韧性和高透明度

Benefits of technology

[0021](1)本发明将适量刚性结构与热可逆的交联结构相结合,为氟树脂的结构设计提供了新的思路。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005471428840000061
    Figure BDA0005471428840000061
Patent Text Reader

Abstract

The application relates to a crosslinked fluororesin, a preparation method and application, and belongs to the technical field of fluorine-containing polymers. The crosslinked fluororesin is composed of a fluorine-containing copolymer A and a crosslinking agent B, the tensile strength of the crosslinked fluororesin is greater than or equal to 30 MPa, the elongation at break is greater than or equal to 150%, and the transparency when the thickness is 0.1 mm is greater than or equal to 85%. The fluorine-containing copolymer A is a copolymer formed by copolymerization of perfluoro-2,2-dimethyl-1,3-dioxolane PDD, hexafluoropropylene and a perfluoroalkyl vinyl ether containing two double bonds. The crosslinked fluororesin prepared by the application has the advantages of high strength, high toughness and high transparency, and expands the performance boundary and application field of the fluororesin.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of fluoropolymer technology, specifically relating to a cross-linked fluoropolymer, its preparation method, and its application. Background Technology

[0002] Fluoropolymers possess excellent weather resistance, chemical corrosion resistance, and non-stick properties due to their unique chemical structure (high bond energy and low surface energy of CF bonds). They can adapt to extreme environments, integrate multiple functions, and exhibit long-term durability, making them highly promising for applications in optics and display technology, electronics and electrical engineering, special protection, and smart surfaces. However, traditional fluoropolymers have limitations in optical and mechanical properties. As modern technology advances towards high-precision, multifunctional, and extreme environment applications, developing fluoropolymers that combine high transparency, high strength, and high toughness has become an important trend in the materials science field. In the field of optics, combining the high transparency, high strength, and high toughness of fluoropolymers with their low refractive index properties can replace bulky and fragile glass materials, meeting the dual demands of lightweight and high definition for flexible displays, photovoltaic modules, and AR / VR optical devices. In the medical field, the combination of high transparency, high strength, and high toughness with the biocompatibility and high chemical stability of fluoropolymers makes them suitable for implantable medical devices and in vitro diagnostic equipment. In specialized applications, the combination of high transparency and high strength and toughness, coupled with the inherent high and low temperature resistance (-200℃~260℃), UV resistance, and radiation resistance of fluoropolymers, makes them irreplaceable in extreme environments such as aerospace (spacecraft windows) and the nuclear industry (radiation monitoring windows). Therefore, developing high-transparency, high-strength, and high-toughness fluoropolymers is not only key to breaking through the performance bottlenecks of traditional materials but also a core foundation supporting the upgrading of strategic industries such as semiconductor manufacturing, new energy, and high-end equipment.

[0003] Most fluoropolymers have relatively flexible molecular chains and low glass transition temperatures. They only exhibit high strength at high crystallinity. However, high crystallinity causes light scattering, significantly reducing the transparency and toughness of the fluoropolymer. This makes it difficult for most commercially available fluoropolymers to simultaneously achieve high strength, high toughness, and high transparency. Therefore, developing fluoropolymers that combine high strength, high toughness, and high transparency remains a significant challenge. Summary of the Invention

[0004] To address the problems in existing technologies, this invention provides a crosslinked fluororesin, its preparation method, and its applications. First, a fluororesin containing an appropriate amount of rigid heterocyclic structures and appropriate amounts of side-chain vinyl groups is prepared through copolymerization. Then, based on the click chemistry of thiol groups and side vinyl groups at high temperatures, a fluororesin is synthesized by crosslinking with multifunctional mercaptoacrylates, thereby preparing a fluororesin with high strength, high toughness, and high transparency. Because this crosslinking structure is dynamically reversible, it can be opened at high temperatures and reconstructed at low temperatures; therefore, this crosslinked fluororesin also exhibits excellent reprocessing performance.

[0005] To achieve the above objectives, the technical solution of the present invention is as follows:

[0006] A crosslinked fluororesin, wherein the crosslinked fluororesin is composed of a fluorinated copolymer A and a crosslinking agent B, and the crosslinked fluororesin has a tensile strength ≥30MPa, an elongation at break ≥150%, and a transparency ≥85% when the thickness is 0.1mm.

[0007] Further, the fluorinated copolymer A is a copolymer formed by copolymerizing perfluoro-2,2-dimethyl-1,3-dioxane-pentene (PDD), hexafluoropropylene, and a perfluoroalkyl vinyl ether containing two double bonds, wherein the molar content of PDD is 10-35%, the molar content of hexafluoropropylene is 40-60%, and the molar content of the perfluoroalkyl vinyl ether containing two double bonds is 10-30%. The perfluoroalkyl vinyl ether containing two double bonds is one or a combination of two of CF2=CFOCF2CF=CF2 and CF2=CFOCF2CF2CF=CF2.

[0008] Furthermore, the crosslinking agent B is one or a combination of two of pentaerythritol tetra(3-mercaptopropionic acid) ester and trimethylolpropane tri(3-mercaptopropionic acid) ester.

[0009] Furthermore, by mass parts, the cross-linked fluororesin contains 100 parts of fluorinated copolymer A and 4 to 10 parts of cross-linking agent.

[0010] A method for preparing a cross-linked fluoropolymer resin, comprising the following specific steps:

[0011] (1) Plasticize the fluorinated copolymer A in a mixer;

[0012] (2) Add crosslinking agent B to the internal mixer and mix it evenly with fluoropolymer A;

[0013] (3) The blend of fluorinated copolymer A and crosslinking agent B is hot-pressed to complete crosslinking and molding.

[0014] Further, the preparation method of the fluorinated copolymer A is as follows: 1,1,2-trichlorotrifluoroethane, PDD, perfluoroalkyl vinyl ether containing two double bonds, and diisopropyl peroxide dicarbonate catalyst are added sequentially to a high-pressure reactor pre-cooled to 0°C, and stirred until uniformly mixed; nitrogen is used to purge the oxygen content in the reactor several times to reduce it to below 5 ppm, and then hexafluoropropylene is slowly added; the reaction is carried out at 40-60°C for 5-7 hours, and the resulting blend solution is poured into methanol to flocculate the prepared fluorinated polymer. The flocculants are then washed with methanol, and the washed product is dried in an oven at 70-90°C to constant weight to obtain fluorinated polymer A.

[0015] Furthermore, in step (1), the plasticizing temperature is 100–140°C, the time is 3–5 minutes, and the rotation speed is 60–100 rpm;

[0016] Furthermore, the blending temperature and rotation speed in step (2) are the same as those in step (1) for plasticizing temperature and rotation speed, and the blending time is 6 to 8 minutes until the torque balance position is reached.

[0017] Furthermore, the hot pressing temperature in step (3) is 140-180°C, and the hot pressing time is 10-20 minutes.

[0018] An application of a cross-linked fluoropolymer, wherein the cross-linked fluoropolymer is used as a packaging material for optical lenses, optical windows, electronic components, flexible circuit boards, surgical instrument housings, vascular stents, and battery separators.

[0019] Those skilled in the art may also add other optional additives as needed to obtain better performance. These additives may be selected from anti-reflective agents, anti-reflective layers, reinforcing agents, plasticizers, anti-aging agents, pigments, etc., and may be added simultaneously or individually.

[0020] The beneficial effects of this invention are:

[0021] (1) This invention combines an appropriate amount of rigid structure with thermally reversible cross-linking structure, providing a new idea for the structural design of fluororesins.

[0022] (2) The cross-linked fluororesin prepared by the present invention has the advantages of high strength, high toughness and high transparency, which expands the performance boundaries and application fields of fluororesin. Detailed Implementation

[0023] The present invention will be further illustrated below with reference to specific embodiments. It should be understood that the following specific embodiments are only for illustrating the present invention and are not intended to limit the scope of the present invention. If those skilled in the art make some non-essential adjustments and improvements to the present invention based on the above content, they shall still fall within the protection scope of the present invention.

[0024] Example 1:

[0025] A method for preparing a cross-linked fluoropolymer resin, comprising the following steps:

[0026] (1) 400 ml of 1,1,2-trichlorotrifluoroethane, 12.8 g of PDD, 34.2 g of CF2=CFOCF2CF=CF2 and 0.46 g of diisopropyl peroxide dicarbonate were added sequentially to a high-pressure reactor pre-cooled to 0 °C. The mixture was stirred at 200 rpm for 15 minutes to ensure uniform mixing. Nitrogen gas was used to purge the oxygen content in the reactor several times to reduce it to below 5 ppm. Then, 45 g of hexafluoropropylene was slowly added through a flow meter. The stirring speed was adjusted to 300 rpm. After reacting at 50 °C for 6 hours, the blend solution was poured into methanol to flocculate the prepared fluoropolymer. The flocculent was washed three times with methanol. The washed product was dried in an oven at 80 °C to constant weight to obtain fluoropolymer A.

[0027] (2) Plasticize 50g of fluorinated copolymer A in a 100℃ internal mixer for 3 minutes at a speed of 60 rpm;

[0028] (3) Add 5g of crosslinking agent pentaerythritol tetra(3-mercaptopropionic acid) ester to the internal mixer and mix it evenly with fluoropolymer A at a temperature of 100℃, a speed of 60 rpm, and a mixing time of 6 minutes.

[0029] (4) The above A and B blends were hot-pressed at 140°C for 10 minutes to obtain a sheet-like cross-linked resin with a thickness of 0.1 mm.

[0030] Example 2:

[0031] A method for preparing a cross-linked fluoropolymer resin, comprising the following steps:

[0032] (1) 400 ml of 1,1,2-trichlorotrifluoroethane, 25.6 g of PDD, 34.2 g of CF2=CFOCF2CF=CF2 and 0.49 g of diisopropyl peroxide dicarbonate were added sequentially to a high-pressure reactor pre-cooled to 0 °C. The mixture was stirred at 200 rpm for 15 minutes to ensure uniform mixing. Nitrogen gas was used to purge the oxygen content in the reactor several times to reduce it to below 5 ppm. Then, 37.5 g of hexafluoropropylene was slowly added through a flow meter. The stirring speed was adjusted to 300 rpm. After reacting at 50 °C for 6 hours, the blend solution was poured into methanol to flocculate the prepared fluoropolymer. The flocculent was washed three times with methanol. The washed product was dried in an oven at 80 °C to constant weight to obtain fluoropolymer A.

[0033] (1) Plasticize 50g of fluorinated copolymer A in a 120℃ internal mixer for 4 minutes at a speed of 60 rpm;

[0034] (2) Add 5g of crosslinking agent pentaerythritol tetra(3-mercaptopropionic acid) ester to the internal mixer and mix it evenly with fluoropolymer A at a temperature of 120℃, a speed of 60 rpm, and a mixing time of 6 minutes.

[0035] (3) The above A and B blends were hot-pressed at 160°C for 10 minutes to obtain a sheet-like cross-linked resin with a thickness of 0.1 mm.

[0036] Example 3:

[0037] A method for preparing a cross-linked fluoropolymer resin, comprising the following steps:

[0038] (1) 400 ml of 1,1,2-trichlorotrifluoroethane, 38.4 g of PDD, 34.2 g of CF2=CFOCF2CF=CF2 and 0.51 g of diisopropyl peroxide dicarbonate were added sequentially to a high-pressure reactor pre-cooled to 0 °C. The mixture was stirred at 200 rpm for 15 minutes to ensure uniform mixing. Nitrogen gas was used to purge the oxygen content in the reactor several times to reduce it to below 5 ppm. Then, 30 g of hexafluoropropylene was slowly added through a flow meter. The stirring speed was adjusted to 300 rpm. After reacting at 50 °C for 6 hours, the blend solution was poured into methanol to flocculate the prepared fluoropolymer. The flocculent was washed three times with methanol. The washed product was dried in an oven at 80 °C to constant weight to obtain fluoropolymer A.

[0039] (1) Plasticize 50g of fluorinated copolymer A in a 140℃ internal mixer for 5 minutes at a speed of 60 rpm;

[0040] (2) Add 5g of crosslinking agent pentaerythritol tetra(3-mercaptopropionic acid) ester to the internal mixer and mix it evenly with fluoropolymer A at a temperature of 140℃, a speed of 60 rpm, and a mixing time of 6 minutes.

[0041] (3) The above A and B blends were hot-pressed at 180°C for 10 minutes to obtain a sheet-like cross-linked resin with a thickness of 0.1 mm.

[0042] Example 4:

[0043] A method for preparing a cross-linked fluoropolymer resin, comprising the following steps:

[0044] (1) 400 ml of 1,1,2-trichlorotrifluoroethane, 25.6 g of PDD, 22.8 g of CF2=CFOCF2CF=CF2 and 0.47 g of diisopropyl peroxide dicarbonate were added sequentially to a high-pressure reactor pre-cooled to 0 °C. The mixture was stirred at 200 rpm for 15 minutes to ensure uniform mixing. Nitrogen gas was used to purge the oxygen content in the reactor several times to reduce it to below 5 ppm. Then, 45 g of hexafluoropropylene was slowly added through a flow meter. The stirring speed was adjusted to 300 rpm. After reacting at 50 °C for 6 hours, the blend solution was poured into methanol to flocculate the prepared fluoropolymer. The flocculent was washed three times with methanol. The washed product was dried in an oven at 80 °C to constant weight to obtain fluoropolymer A.

[0045] (1) Plasticize 50g of fluorinated copolymer A in a 140℃ internal mixer for 4 minutes at a speed of 80 rpm;

[0046] (2) Add 5g of crosslinking agent pentaerythritol tetra(3-mercaptopropionic acid) ester to the internal mixer and mix it evenly with fluoropolymer A at a temperature of 140℃, a speed of 60 rpm, and a mixing time of 6 minutes.

[0047] (3) The above A and B blends were hot-pressed at 180°C for 10 minutes to obtain a sheet-like cross-linked resin with a thickness of 0.1 mm.

[0048] Example 5:

[0049] A method for preparing a cross-linked fluoropolymer resin, comprising the following steps:

[0050] (1) 400 ml of 1,1,2-trichlorotrifluoroethane, 25.6 g of PDD, 22.8 g of CF2=CFOCF2CF=CF2 and 0.47 g of diisopropyl peroxide dicarbonate were added sequentially to a high-pressure reactor pre-cooled to 0 °C. The mixture was stirred at 200 rpm for 15 minutes to ensure uniform mixing. Nitrogen gas was used to purge the oxygen content in the reactor several times to reduce it to below 5 ppm. Then, 45 g of hexafluoropropylene was slowly added through a flow meter. The stirring speed was adjusted to 300 rpm. After reacting at 50 °C for 6 hours, the blend solution was poured into methanol to flocculate the prepared fluoropolymer. The flocculent was washed three times with methanol. The washed product was dried in an oven at 80 °C to constant weight to obtain fluoropolymer A.

[0051] (1) Plasticize 50g of fluorinated copolymer A in a 140℃ internal mixer for 4 minutes at a speed of 80 rpm;

[0052] (2) Add 4g of crosslinking agent pentaerythritol tetra(3-mercaptopropionic acid) ester to the internal mixer and mix it evenly with fluoropolymer A at a temperature of 140℃, a speed of 60 rpm, and a mixing time of 6 minutes.

[0053] (3) The above A and B blends were hot-pressed at 180°C for 10 minutes to obtain a sheet-like cross-linked resin with a thickness of 0.1 mm.

[0054] Example 6:

[0055] A method for preparing a cross-linked fluoropolymer resin, comprising the following steps:

[0056] (1) 400 ml of 1,1,2-trichlorotrifluoroethane, 25.6 g of PDD, 22.8 g of CF2=CFOCF2CF=CF2 and 0.47 g of diisopropyl peroxide dicarbonate were added sequentially to a high-pressure reactor pre-cooled to 0 °C. The mixture was stirred at 200 rpm for 15 minutes to ensure uniform mixing. Nitrogen gas was used to purge the oxygen content in the reactor several times to reduce it to below 5 ppm. Then, 45 g of hexafluoropropylene was slowly added through a flow meter. The stirring speed was adjusted to 300 rpm. After reacting at 50 °C for 6 hours, the blend solution was poured into methanol to flocculate the prepared fluoropolymer. The flocculent was washed three times with methanol. The washed product was dried in an oven at 80 °C to constant weight to obtain fluoropolymer A.

[0057] (1) Plasticize 50g of fluorinated copolymer A in a 140℃ internal mixer for 4 minutes at a speed of 80 rpm;

[0058] (2) Add 2g of crosslinking agent pentaerythritol tetra(3-mercaptopropionic acid) ester to the internal mixer and mix it evenly with fluoropolymer A at a temperature of 140℃, a speed of 60 rpm, and a mixing time of 6 minutes.

[0059] (3) The above A and B blends were hot-pressed at 180°C for 10 minutes to obtain a sheet-like cross-linked resin with a thickness of 0.1 mm.

[0060] Example 7:

[0061] A method for preparing a cross-linked fluoropolymer resin, comprising the following steps:

[0062] (1) 400 ml of 1,1,2-trichlorotrifluoroethane, 25.6 g of PDD, 22.8 g of CF2=CFOCF2CF=CF2 and 0.47 g of diisopropyl peroxide dicarbonate were added sequentially to a high-pressure reactor pre-cooled to 0 °C. The mixture was stirred at 200 rpm for 15 minutes to ensure uniform mixing. Nitrogen gas was used to purge the oxygen content in the reactor several times to reduce it to below 5 ppm. Then, 45 g of hexafluoropropylene was slowly added through a flow meter. The stirring speed was adjusted to 300 rpm. After reacting at 50 °C for 6 hours, the blend solution was poured into methanol to flocculate the prepared fluoropolymer. The flocculent was washed three times with methanol. The washed product was dried in an oven at 80 °C to constant weight to obtain fluoropolymer A.

[0063] (1) Plasticize 50g of fluorinated copolymer A in a 140℃ internal mixer for 4 minutes at a speed of 80 rpm;

[0064] (2) Add 4g of crosslinking agent trimethylolpropane tris(3-mercaptopropionic acid) ester to the internal mixer and mix it evenly with fluoropolymer A at a temperature of 140℃, a speed of 60 rpm, and a mixing time of 6 minutes.

[0065] (3) The above A and B blends were hot-pressed at 180°C for 10 minutes to obtain a sheet-like cross-linked resin with a thickness of 0.1 mm.

[0066] Comparative Example 1:

[0067] A method for preparing an uncrosslinked fluoropolymer resin, comprising the following steps:

[0068] (1) 400 ml of 1,1,2-trichlorotrifluoroethane, 25.6 g of PDD, 22.8 g of perfluoroalkyl vinyl ether containing two double bonds and 0.47 g of diisopropyl peroxide dicarbonate were added sequentially to a high-pressure reactor pre-cooled to 0 °C. The mixture was stirred at 200 rpm for 15 minutes to ensure uniform mixing. Nitrogen gas was used to purge the oxygen content in the reactor several times to reduce it to below 5 ppm. Then, 45 g of hexafluoropropylene was slowly added through a flow meter. The stirring speed was adjusted to 300 rpm. After reacting at 50 °C for 6 hours, the blend solution was poured into methanol to flocculate the prepared fluoropolymer. The flocculent was washed three times with methanol. The washed product was dried in an oven at 80 °C to constant weight to obtain fluoropolymer A.

[0069] (1) Plasticize 50g of fluorinated copolymer A in a 140℃ internal mixer for 4 minutes at a speed of 80 rpm;

[0070] (2) Continue to plasticize fluoropolymer A at a temperature of 140°C, a speed of 60 rpm, and a stirring time of 6 minutes;

[0071] (3) The above-mentioned plasticized fluoropolymer A was hot-pressed at 180°C for 10 minutes to obtain a sheet of fluoropolymer with a thickness of 0.1 mm.

[0072] Table 1. Typical performance of Comparative Examples 1-4 and Examples 1-11

[0073]

[0074] The above results indicate that: 1) Uncrosslinked ternary copolymer fluoropolymers (Comparative Example 1), while exhibiting good toughness, have lower transparency and tensile strength, while crosslinked fluoropolymers (Examples 1-6) possess excellent transparency, tensile strength, and toughness. 2) Examples 1-3 demonstrate that the rigid structural unit PDD can effectively improve the transparency and strength of the resin, but significantly reduces the elongation at break. 3) Examples 4-6 demonstrate that the crosslinked structure can improve the transparency and strength of the resin, but slightly reduces the toughness of the crosslinked resin. 4) Examples 5 and 7 demonstrate that the higher the functionality of the crosslinking agent, the higher the probability of effective crosslinking, which helps to improve the strength and transparency of the crosslinked fluoropolymer.

[0075] Those skilled in the art should understand that the above description is merely a specific embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc., made within the spirit and principles of the present invention should be included within the protection scope of the present invention.

Claims

1. A cross-linked fluororesin, characterized in that, The cross-linked fluororesin is composed of a fluorinated copolymer A and a cross-linking agent B. The cross-linked fluororesin has a tensile strength ≥30 MPa, an elongation at break ≥150%, and a transparency ≥85% at a thickness of 0.1 mm. The fluorinated copolymer A is a copolymer formed by copolymerizing perfluoro-2,2-dimethyl-1,3-dioxane (PDD), hexafluoropropylene, and a perfluoroalkyl vinyl ether containing two double bonds, wherein the molar content of PDD is 10-35%, the molar content of hexafluoropropylene is 40-60%, and the molar content of the perfluoroalkyl vinyl ether containing two double bonds is 10-30%; the perfluoroalkyl vinyl ether containing two double bonds is one or a combination of two of CF2=CFOCF2CF=CF2 and CF2=CFOCF2CF2CF=CF2. The crosslinking agent B is one or a combination of two of pentaerythritol tetra(3-mercaptopropionic acid) ester and trimethylolpropane tri(3-mercaptopropionic acid) ester; The cross-linked fluororesin contains 100 parts by mass of fluorinated copolymer A and 4 to 10 parts by mass of cross-linking agent.

2. The method for preparing a cross-linked fluoropolymer according to claim 1, characterized in that, The specific steps are as follows: (1) Plasticize the fluorinated copolymer A in a mixer; (2) Add crosslinking agent B to the internal mixer and mix it evenly with fluoropolymer A; (3) The blend of fluorinated copolymer A and crosslinking agent B is hot-pressed to complete crosslinking and molding.

3. The method for preparing a cross-linked fluoropolymer according to claim 2, characterized in that, The preparation method of the fluorinated copolymer A is as follows: 1,1,2-trichlorotrifluoroethane, PDD, perfluoroalkyl vinyl ether containing two double bonds, and diisopropyl peroxide dicarbonate catalyst are added sequentially to a high-pressure reactor pre-cooled to 0°C and stirred until homogeneous. Nitrogen gas is used to purge the oxygen content in the reactor several times to reduce it to below 5 ppm, and then hexafluoropropylene is slowly added. The reaction is carried out at 40-60°C for 5-7 hours. The resulting blend solution is poured into methanol to flocculate the prepared fluorinated polymer. The flocculants are then washed with methanol, and the washed product is dried in an oven at 70-90°C to constant weight to obtain fluorinated polymer A.

4. The method for preparing a cross-linked fluoropolymer according to claim 2, characterized in that, The plasticizing temperature in step (1) is 100~140 ℃, the time is 3~5 minutes, and the rotation speed is 60~100 rpm.

5. The method for preparing a cross-linked fluoropolymer according to claim 2, characterized in that, The blending temperature and speed in step (2) are the same as those in step (1) for plasticizing temperature and speed, and the blending time is 6 to 8 minutes until the torque balance position is reached.

6. The method for preparing a cross-linked fluoropolymer according to claim 2, characterized in that, The hot pressing temperature in step (3) is 140~180 ℃ and the hot pressing time is 10~20 minutes.

7. The application of a cross-linked fluororesin according to claim 1, or a cross-linked fluororesin prepared by any one of claims 2-6, characterized in that, The cross-linked fluororesin is used in the preparation of optical lenses, optical windows, encapsulation materials for electronic components, flexible circuit boards, surgical instrument shells, vascular stents, and battery separators.

Citation Information

Patent Citations

  • Crosslinkable vinyl fluoride copolymers

    CN101563375A

  • Fluorine-containing copolymer

    CN118900861A